2013
DOI: 10.1159/000351852
|View full text |Cite
|
Sign up to set email alerts
|

MPT0B169, a New Tubulin Inhibitor, Inhibits Cell Growth and Induces G2/M Arrest in Nonresistant and Paclitaxel-Resistant Cancer Cells

Abstract: The polymerization of tubulin molecules forms microtubules which are considered an attractive target for cancer treatment. Herein, we synthesized a new tubulin inhibitor, MPT0B169 (2-dimethylamino-N-[1-(4-methoxy-benzenesulfonyl)-2,​3-dihydro-1H-indol-7-yl]-acetamide) and demonstrated its action in leukemia cell lines HL60 and NB4 and lymphoma cell line U937. We found that MPT0B169 prevented tubulin assembly by binding the colchicine-binding site of tubulin in vitro. MPT0B169 also induced tubulin depolymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…MPT0B169 and MPT0B002 were synthesized as previously described [9,10] and dissolved in dimethyl sulfoxide (DMSO; SigmaAldrich, St. Louis, MO, USA).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…MPT0B169 and MPT0B002 were synthesized as previously described [9,10] and dissolved in dimethyl sulfoxide (DMSO; SigmaAldrich, St. Louis, MO, USA).…”
Section: Chemicalsmentioning
confidence: 99%
“…In our previous studies, we synthesized 2 indole-based compounds, 2-di- Fig. 1a) [9] and (1-methyl-1H-indol-5-yl)-(3,4,5-trimethoxy-phenyl)-methanone (MPT0B002; Fig. 1b) [10] as novel tubulin inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, antitumor drugs are liable to the development of drug resistance, which restricts clinical treatment (17). Therefore, treatment methods that target specific cell signaling pathways require investigation, and studies have identified novel targets for targeted therapy of tumor molecules, including the regulation of miRs (18,19). Therefore, miRs provide a novel method for treating malignant tumors, and it has been observed that treating cancer by regulating the level of miRs in the cancerous cells is possible (20).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much effort has been devoted to the identification of new ligands binding to the colchicine site of tubulin, derived not only from natural sources but also by screening of compound libraries in combination with traditional medicinal chemistry [9,10]. Quinoline and benzopyridooxathiazepine (BPT) derivatives are a pharmacologically active class of heterocyclic compounds that have been reported to inhibit tubulin polymerization, leading to cell cycle arrest and apoptosis [8,11,12]. Among the series of synthesized products, 2-dimethylamino-N-[1-(4-methoxy-benzenesulfonyl)-2,3-dihydro-1H-indol-7-yl]acetamide was a novel class of quinoline derivative identified as a potent microtubule inhibitor acting through the colchicine-binding site of tubulin [8].…”
Section: Introductionmentioning
confidence: 99%